Towards community-based and recovery-oriented care for severe mental disorders in Southern and Eastern Europe: aims and design of a multi-country implementation and evaluation study (RECOVER-E) - Shields-Zeeman, Laura; Petrea, Ionela; Smit, Filip; Walters, Bethany Hipple; Dedovic, Jovo; Kuzman, Martina Rojnic; Nakov, Vladimir; Nica, Raluca; Novotni, Antoni; Roth, Catharina; Tomcuk, Aleksandar; Wijnen, Ben F. M.; et al. (International journal of mental health systems, 2020)
Substantial strides have been made around the world in reforming mental health systems by shifting away from institutional care towards community-based services. Despite an extensive evidence base on what constitutes effective care for people with severe mental ill-health, many people in Europe do not have access to optimal mental health care. In an effort to consolidate previous efforts to improve community mental health care and support the complex transition from hospital-based to community-based care delivery, the RECOVER-E (LaRge-scalE implementation of COmmunity based mental health care for people with seVere and Enduring mental ill health in EuRopE) project aims to implement and evaluate multidisciplinary community mental health teams in five countries in Central and Eastern Europe. This paper provides a brief overview of the RECOVER-E project and its methods.
Gesehen am 15.06.2020